PERBANDINGAN ANALISIS PENILAIAN HARGA WAJAR SAHAM DENGAN METODE PENILAIAN RELATIF DAN ARUS KAS TERDISKONTO DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Budiono, Dymas Adji Zaksana; Yuana, Pusvita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Based on history the JKSE level will reverse direction if it experiences a deep decline that occurs in global or national conditions, in 2020 the JKSE will experience a deep decline due to the COVID-19 pandemic. This makes a potential investment in the healthcare sector, based on price movements through IDXHEALTH, the price of this sector continues to increase because the industry is in high demand. Thus, this study aims to find the fair value of shares in the healthcare sector to invest in by using a comparison of two valuation methods, namely relative valuation and discounted cash flow. The sampling technique was non-probability sampling, namely purposive sampling on the population of the pharmaceutical and health research sectors on the Indonesia Stock Exchange. The data analysis method used is descriptive statistical analysis, relative valuation, and discounted cash flow. The results of this study indicate that both methods can be used. However, discounted cash flows are more realistic based on a safer margin of safety in risk comparisons and result in undervalued conclusions so that buying decisions for investors and companies can be a reference to improve company performance.